CHARACTER EDUCATION VALUES FROM THE PERSPECTIVE OF THE QURAN: A STUDY OF TAFSIR TARBAWI QS. LUQMAN VERSES 12-19 - Selena Aulia; Asmuki Asmuki; Cucu Surahman; Elan Sumarna (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2024)
Many studies on character education have been carried out. From the study of character education in general, specifically character education in Islamic boarding schools, and more specifically, the exploration of character contained in Qur’an verses such as QS Luqman verses 12-19. This research is focused on the study of QS content. Kuqman verses 12-19. The question we want to answer from this study is: what are the characters in QS Luqman verses 12-19, and how is it implemented in education? Literature research was conducted to answer this question, namely interpretations about QS. Luqman verses 12-19 are studied and elaborated with the thoughts of Syaltut and Khallaf to lead researchers to the findings of implementing the character contained in QS. Luqman verses 12-19. From the data found and studied, it can be concluded that eleven characters should be instilled in children. Of these eleven characters, it is dominated by moral cultivation rather than characters with a faith dimension of only 18%, let alone characters with a sharia dimension of only 9%. It shows that the application of character education for children is more emphasized in the habit of behaving, speaking kindly and politely, and caring for others.